2020
DOI: 10.1093/neuonc/noaa222.614
|View full text |Cite
|
Sign up to set email alerts
|

NFB-11. White Matter Differences in Children With Nf1 Compared to Controls

Abstract: INTRODUCTION Neurofibromatosis type 1 (NF1) is a genetic condition in which children develop learning challenges and glioma. White matter tracts (WMT) are implicated in these cognitive functions, while oligodendroglial precursor cells are implicated in both gliomagenesis and white-matter development. Specific WMTs have not been well characterized in NF1. METHODS Twenty NF1 patients aged 1.4–17.6 years (M = 9.5 years, 24 male)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prior diffusion tensor imaging studies on children with NF1 and NS found widespread reduced fractional anisotropy and increased mean diffusivity in both conditions (8, 23,25). Fractional anisotropy and mean diffusivity are sensitive to disruptions in microstructural integrity; however, they are also non-speci c measures and di cult to interpret in voxels with complex microstructural properties (e.g., crossing bers) (28, 29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prior diffusion tensor imaging studies on children with NF1 and NS found widespread reduced fractional anisotropy and increased mean diffusivity in both conditions (8, 23,25). Fractional anisotropy and mean diffusivity are sensitive to disruptions in microstructural integrity; however, they are also non-speci c measures and di cult to interpret in voxels with complex microstructural properties (e.g., crossing bers) (28, 29).…”
Section: Discussionmentioning
confidence: 97%
“…These ROIs comprise grey and white matter, whereas the tracts are predominantly white matter. ROIs and white matter tracts were selected based on prior diffusion tensor imaging studies where signi cant alterations to parameters such as fractional anisotropy and mean diffusivity were found in NF1 and NS (8, [23][24][25]. TRActs Constrained by UnderLying Anatomy (TRACULA) delineated 42 major white matter tracts using probabilistic tractography (26).…”
Section: Image Analysismentioning
confidence: 99%